Design and performance of a SAW ladder-type filter at 3.15 GHz using SAW mass production technology - Hollerweger, Franz; Springer, Andreas; Weigel, Robert; Ruile, Werner; Thomas, Ralf; Berek, S.; Guglielmi, Marco (IEEE MTT-S Microwave Symposium, 1999)
To meet the increasing demand of high performance filters in GHz radio communication systems, we have improved the design techniques and fabrication processes for SAW devices. The standard optical projection printing technique based on i-line lithography used for mass-production was optimized, thus attaining a linewidth of 0.3 microns. As a first SAW device prototype we designed and fabricated a ladder type bandpass filter from 42° rotYX-LiTaO3 substrate, at 3.15 GHz having a bandwidth of close to 200 MHz and a minimum insertion loss of 1.7 dB
elib2cris::1512001600,hollerweger1999